The League of Nations, Traffic in Women and the Transnationalization of Criminal Law - Paul Knepper (Rechtsgeschichte - Legal History)
During the 1920s, the Advisory Committee on the Traffic in Women, of the League of Nations operated as a legal regime in the transnationalization of criminal law. This can be seen in its management of the first ›worldwide‹ investigation into the traffic in women which sent undercover investigators to more than a 100 countries across Europe, the Americas, and the Mediterranean. The Advisory Committee initiated ›trafficking‹ as a transnational crime and advanced the understanding of transnational criminal law beyond concepts of professional criminality.